2004
DOI: 10.1002/ajp.20089
|View full text |Cite
|
Sign up to set email alerts
|

Comparing maternal styles in bonobos (Pan paniscus) and chimpanzees (Pan troglodytes)

Abstract: Studies on Cercopithecine primate maternal styles, using factor analysis on a set of maternal behaviors, commonly render two factors that describe separate dimensions of maternal behavior: protectiveness and rejection. The aims of this study were to 1) investigate whether this method for determining maternal styles in Cercopithecine species can be applied to bonobos (Pan paniscus) and chimpanzees (Pan troglodytes), 2) determine whether they follow the same pattern, and 3) assess whether species differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…This complexity is evident in their high fission-fusion dynamics (Campbell and Fiske 1959;Wrangham 1975) as well as in other aspects of their social dynamics such as hierarchy (Newton-Fisher 2004), sociosexual interactions (Gomes and Boesch 2009;Stumpf and Boesch 2010), mother-infant relationships (de Lathouwers and van Elsacker 2004;Hirata 2009), play behavior (Cordoni and Palagi 2011;Palagi 2007), and grooming (Nakamura 2003). Infants and juveniles learn species-typical behaviors, including foraging skills, tool use, and cultural traditions (McGrew 2004).…”
Section: Introductionmentioning
confidence: 98%
“…This complexity is evident in their high fission-fusion dynamics (Campbell and Fiske 1959;Wrangham 1975) as well as in other aspects of their social dynamics such as hierarchy (Newton-Fisher 2004), sociosexual interactions (Gomes and Boesch 2009;Stumpf and Boesch 2010), mother-infant relationships (de Lathouwers and van Elsacker 2004;Hirata 2009), play behavior (Cordoni and Palagi 2011;Palagi 2007), and grooming (Nakamura 2003). Infants and juveniles learn species-typical behaviors, including foraging skills, tool use, and cultural traditions (McGrew 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Both studies also reported a third factor labeled Independence/Warmth, which consisted of maternal grooming, cradling, nursing and contact with the infant. Although the challenge of PCA techniques is that they are data-driven and therefore, study-specific, further support for the existence of Rejecting and Protective maternal styles followed in additional reports of rhesus macaques [Berman, 1990; Maestripieri, Higley, Lindell, Newman, McCormack, & Sanchez, 2006; McCormack et al, 2006], and bonobos [deLathouwers & van Elsacker, 2004]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast with reports from the wild, active rejection by bonobo mothers does occur in captivity. Bonobo mothers even reject their infants more than chimpanzee mothers (De Lathouwers and Van Elsacker 2004), which may correspond with the general higher Hence, our results seem to indicate that the weaning period itself seems more stressful for chimpanzee infants when being compared to the distress levels of younger un-weaned conspecifics and bonobos. More detailed analyses are needed to confirm whether the weaning bouts are indeed accompanied with simultaneous higher distress levels.…”
Section: Discussionmentioning
confidence: 48%